Renal and metabolic toxicities following initiation of HIV-1 treatment regimen in a diverse, multinational setting: A focused safety analysis of ACTG PEARLS (A5175) - Touzard Romo,F. (Thomas Land Publishers Inc., 2015)
© 2014 Thomas Land Publishers, Inc. Background: Convenient dosing, potency, and low toxicity support use of tenofovir disoproxil fumarate (TDF) as preferred nucleotide reverse transcriptase inhibitor (NRTI) for HIV-1 treatment. However, renal and metabolic safety of TDF compared to other NRTIs has not been well described in resource-limited settings. Methods: This was a secondary analysis examining the occurrence of renal abnormalities (RAs) and renal and metabolic serious non-AIDS-defining events (SNADEs) through study follow-up between participants randomized to zidovudine (ZDV)/lamivudine/ efavirenz and TDF/emtricitabine/efavirenz treatment arms within A5175/PEARLS trial. Exact logistic regression explored associations between baseline covariates and RAs. Response profile longitudinal analysis compared creatinine clearance (CrCl) over time between NRTI groups. Results: Twenty-one of 1,045 participants developed RAs through 192 weeks follow-up; there were 15 out of 21 in the TDF arm (P = .08). Age 41 years or older (odds ratio [OR], 3.35; 95% CI, 1.1-13.1), his- tory of diabetes (OR, 10.7; 95% CI, 2.1-55), and lower baseline CrCl (OR, 3.1 per 25 mL/min decline; 95% CI, 1.7-5.8) were associated with development of RAs. Renal SNADEs occurred in 42 participants; 33 were urinary tract infections and 4 were renal failure/insufficiency; one event was attributed to TDF. Significantly lower CrCl values were maintained among patients receiving TDF compared to ZDV (repeated measures analysis, P = .05), however worsening CrCl from baseline was not observed with TDF exposure over time. Metabolic SNADEs were rare, but were higher in the ZDV arm (20 vs 3; P < .001). Conclusions: TDF is associated with lower serious metabolic toxicities but not higher risk of RAs, serious renal events, or worsening CrCl over time compared to ZDV in this randomized multinational study.